alpha-Globin genes: thalassemic and structural alterations in a Brazilian population - Wenning,M.R.S.C. (2000)
Seven unrelated patients with hemoglobin (Hb) H disease and 27 individuals with alpha-chain structural alterations were studied to identify the alpha-globin gene mutations present in the population of Southeast Brazil. The -alpha3.7, --MED and -(alpha)20.5 deletions were investigated by PCR, whereas non-deletional alpha-thalassemia (alphaHphalpha, alphaNcoIalpha, aaNcoI, alphaIcalpha and alphaTSaudialpha) was screened with restriction enzymes and by nested PCR. Structural alterations were identified by direct DNA sequencing. Of the seven patients with Hb H disease, all of Italian descent, two had the -(alpha)20.5/-alpha3.7 genotype, one had the --MED/-alpha3.7 genotype, one had the --MED/alphaHphalpha genotype and three showed interaction of the -alpha3.7 deletion with an unusual, unidentified form of non-deletional alpha-thalassemia [-alpha3.7/(aa)T]. Among the 27 patients with structural alterations, 15 (of Italian descent) had Hb Hasharon (alpha47Asp->His) associated with the -alpha3.7 deletion, 4 (of Italian descent) were heterozygous for Hb J-Rovigo (alpha53Ala->Asp), 4 (3 Blacks and 1 Caucasian) were heterozygous for Hb Stanleyville-II (alpha78Asn->Lys) associated with the alpha+-thalassemia, 1 (Black) was heterozygous for Hb G-Pest (alpha74Asp->Asn), 1 (Caucasian) was heterozygous for Hb Kurosaki (alpha7Lys->Glu), 1 (Caucasian) was heterozygous for Hb Westmead (alpha122His->Gln), and 1 (Caucasian) was the carrier of a novel silent variant (Hb Campinas, alpha26Ala->Val). Most of the mutations found reflected the Mediterranean and African origins of the population. Hbs G-Pest and Kurosaki, very rare, and Hb Westmead, common in southern China, were initially described in individuals of ethnic origin differing from those of the carriers reported in the present study and are the first cases to be reported in the Brazilian population.